Pengaruh Disiplin Kerja dan Pengawasan Terhadap Efektivitas Kerja Karyawan di Cabang Utama PT. JNE Kota Palembang - Aras Tulip; Tutik Pebrianti; Indah Mawarni; Vivin Afini; Zein Ghozali (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2022)
This study aims to determine how big the influence of work discipline and supervision on the work effectiveness of employees in the main branch of PT. JNE Palembang City. This study used a survey method (questionnaire). population and sample in this study amounted to 30 people. Based on the results of the t test variable Work Discipline (X1) and Supervision (X2) on employee effectiveness (Y) obtained t count 5.126 > t table 2.042 then ho is rejected and ha is accepted. This means that the variables of work discipline and supervision partially have an influence on the work effectiveness of the employees of the main branch of PT. JNE Palembang City. So it can be concluded that the variables of work discipline and supervision have a significant effect on customer satisfaction. Based on the results of the Determination Coefficient Test (R), it can be seen that the influence of the work discipline variable on employee work effectiveness is 0.362 or 36.2% while the remaining 63.8% is influenced by other factors, while the magnitude of the influence of the supervisory variable on work effectiveness is 0.417 or 41 .7% while the rest is influenced by other factors. It can be concluded that work discipline and supervision affect the work effectiveness of employees in the main branch of PT. JNE Palembang City.